Rozpoznawanie i ocena czynników ryzyka finansowania rynku nieruchomości - Sitek, Marcin (Determination and Evaluation of Risk Factors in Estate Market Founding, 2008)
Evaluation of found risk and credit services of the estate market allows to select the most significant categories and their sources. Risk reduction activities were indicated on the basis of developer's credits. It was shown that risk sources recognition as well as the risk factor assessment are considered as one of stages in estate market found risk management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 497-506